Effectiveness Comparison of Polysaccharides, Proteins, and Lipids as Composite Edible Coatings on the Quality of Food Products - Budianto, Budianto; Suparmi, Anik; Arifin, Muh Jaenal; Haryani, Ratna (Vitae, 2022)
Background: This research was motivated by the complaints of tomato farmers about their crops that quickly rotted before being sold, as well as the many research results (raw materials and methods) that edible coating films could not be applied optimally. Objectives: The research was a practical recommendation by comparing the effectiveness of raw materials (polysaccharides, proteins, and lipids) with the dipping and spray methods. Materials and methods used in the comparison process were the application of Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. Results: Dipping has a strong effect (f2 ≥ 0.35; p<0.05), while spray had a moderate effect (f2: 0.15-0.35; p<0.05). Thus, the role of dipping as a mediator was more dominant than spray. Compared to proteins and lipids, polysaccharides had the best effectiveness (β:0.460-0.584; f2: 0.15-0.35; p<0.05). Conclusion: the three ingredients improved the quality of tomatoes, and the dipping method was easier to apply by farmers than the spray method, which had many obstacles in its application.